The Vasodilator Effect of a Cream Containing 10% Menthol and 15% Methyl Salicylate on Random-Pattern Skin Flaps in Rats - Dölen, Utku Can; Sungur, Nezih; Koca, Gökhan; Ertunç, Onur; Bağcı Bosi, Ayşe Tülay; Koçer, Uğur; Korkmaz, Meliha (Archives of Plastic Surgery, 2015)
Background It is still difficult to prevent partial or full-thickness flap necrosis. In this study, the effects of a cream containing menthol and methyl salicylate on the viability of randompattern skin flaps were studied.Methods Forty female Sprague-Dawley rats were divided into two equal groups. Caudally based dorsal random-pattern skin flaps were elevated, including the panniculus carnosus. In the study group, 1.5 mL of a cream containing menthol and methyl salicylate was applied to the skin of the flap, and saline solution (0.9%) was used in the control group. Upon completion of the experiment, flap necrosis was analyzed with imaging software and radionuclide scintigraphy. Histopathological measurements were made of the percentage of viable flaps, the number of vessels, and the width of the panniculus carnosus muscle.Results According to the photographic analysis, the mean viable flap surface area in the study group was larger than that in the control group (P=0.004). According to the scintigrams, no change in radioactivity uptake was seen in the study group (P>0.05). However, a significant decrease was observed in the control group (P=0.006). No statistically significant differences were observed between the groups in terms of the percentage of viable flaps, the number of vessels, or the width of the panniculus carnosus muscle (P>0.05).Conclusions Based on these results, it is certain that the cream did not reduce the viability of the flaps. Due to its vasodilatory effect, it can be used as a component of the dressing in reconstructive operations where skin perfusion is compromised.
Keywords: Surgical flaps; Menthol; Methyl salicylate; Vasodilator agents; Perfusion